2013
DOI: 10.1080/01635581.2013.832779
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid and Embelin Affect Key Cellular Components of Pancreatic Adenocarcinoma, Cancer, and Stellate Cells

Abstract: Ellagic acid is a polyphenolic phytochemical present in many fruits and nuts with anti-cancer properties demonstrated in experimental tumor studies. Embelin is a benzoquinone phytochemical isolated from the Japanese herb Ardisiae Japonicae and has been shown to induce apoptosis in cancer cells. We found that ellagic acid and embelin each dose-dependently increased apoptosis and inhibited proliferation in human pancreatic cancer cells, MIA PaCa-2 and HPAF-II cells, and in pancreatic stellate cells (PaSCs) which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 33 publications
(36 reference statements)
0
39
0
Order By: Relevance
“…Approaches that have yet to be tried in the clinical setting, but appear to have exhibited encouraging results in the pre-clinical setting include: i) Pirfenidone e an antifibrotic agent shown to reduce growth of pancreatic tumours produced by a mixture of pancreatic cancer cells and PSCs, but not that of tumours produced by cancer cells alone [40]; ii) the phytonutrients ellagic acid and embelin reported to decrease cancer cell proliferation but to increase apoptosis of cancer cells and PSCs in a xenograft model of pancreatic cancer [41]; iii) all trans retinoic acid (ATRA) reported to decrease tumour growth in a transgenic model of pancreatic cancer [42]; and, most recently iv) vitamin D receptor ligand calcipotriol shown to induce quiescence of PSCs leading to stromal remodelling, reduced tumour volume and increased survival, in an allograft orthotopic model of pancreatic cancer [43].…”
Section: Inhibition Of the Renin-angiotensin Systemmentioning
confidence: 97%
“…Approaches that have yet to be tried in the clinical setting, but appear to have exhibited encouraging results in the pre-clinical setting include: i) Pirfenidone e an antifibrotic agent shown to reduce growth of pancreatic tumours produced by a mixture of pancreatic cancer cells and PSCs, but not that of tumours produced by cancer cells alone [40]; ii) the phytonutrients ellagic acid and embelin reported to decrease cancer cell proliferation but to increase apoptosis of cancer cells and PSCs in a xenograft model of pancreatic cancer [41]; iii) all trans retinoic acid (ATRA) reported to decrease tumour growth in a transgenic model of pancreatic cancer [42]; and, most recently iv) vitamin D receptor ligand calcipotriol shown to induce quiescence of PSCs leading to stromal remodelling, reduced tumour volume and increased survival, in an allograft orthotopic model of pancreatic cancer [43].…”
Section: Inhibition Of the Renin-angiotensin Systemmentioning
confidence: 97%
“…Other approaches, albeit currently limited to pre-clinical studies include (i) the anti-fibrotic agent Pirfenidone reported to decrease the growth of tumors produced by the injection of a mixture of pancreatic cancer cells and PSCs, but not that of tumors produced by cancer cells alone [170]; (ii) the phytonutrients ellagic acid and embelin, which have been reported to decrease proliferation and increase apoptosis of cancer cells as well as stellate cells resulting in significantly reduced tumor volumes in a xenograft model of pancreatic cancer [171]; and (iii) all trans retinoic acid (ATRA) reported to decrease tumor growth in a transgenic model of pancreatic cancer [88].…”
Section: Angiotensin II Receptor Antagonistsmentioning
confidence: 99%
“…Because several studies have described the anti-proliferative and apoptotic-induced potential of EA that naturally occurs in plants, fruits, and vegetables, through modulation of several subcellular signaling pathways, and anti-oxidant defense mechanisms (Edderkaoui et al, 2013;Losso et al, 2004;Mishra and Vinayak, 2014a, b;Narayanan et al, 1999;Vanella et al, 2013;Zhang et al, 2014), these results are of particular relevance for the potential of the Lafoensia pacari extract itself as an anti-cancer remedy, opening the possibility that one or more compounds apart from EA in the extract are responsible for such a strong activity.…”
Section: Influence Of Lafoensia Pacari Extract On U-937 Cells' Physicmentioning
confidence: 99%